BEACH CLUB LIKUPANG: Biomimicry Architecture - Maun, Jofran I.; Tungka, Aristotulus E.; Karongkong, Hendriek H. (PS S1 Arsitektur. Jurusan Arsitektur, Fakultas Teknik Universitas Sam Ratulangi Manado, 2024)
Likupang, located in North Sulawesi, is one of Indonesia's super-priority tourism destinations, offering rich natural resources such as white sandy beaches, coral reefs, and abundant marine biodiversity. This is further evidenced by the increasing number of tourists visiting North Sulawesi each year. However, as a tourist destination, the existing attractions and facilities in Likupang are insufficient to fully leverage its tourism potential. To address this issue, the Likupang Beach Club is proposed as a new attraction and facility to support Likupang as a premier tourism destination. By integrating buildings with nature, the biomimicry approach serves as an appropriate theme to apply natural principles in architectural design. The design of the Likupang Beach Club, based on a biomimicry architectural approach, aims to create a structure that seamlessly integrates with the natural beauty of Likupang and fosters harmony between the building and its surroundings by mimicking natural principles. Through stages of determination, data collection, and implementation, the design process combines the variety development and reduction methods with cycles of imagination, presentation, and testing. This process incorporates typological, site, environmental, and thematic approaches to achieve a unique design that positively impacts the surrounding environment and nature. The application of biomimicry in architecture, which integrates buildings with nature, offers an innovative and visually appealing solution for sustainable tourism development. The design of the Likupang Beach Club demonstrates that working with nature does not mean harming it. Instead, it showcases how a design can collaborate with its environment, resulting in a sustainable and harmonious development. Keywords: Likupang, Toursim, Beach Club, Biomimicry. Architecture